Cassava yield in conventional and no-tillage cultivation in integrated crop-livestock systems - Gobbi, Kátia Fernanda; Takahashi, Mário; Azevedo, Mateus Carvalho Basílio de; Fidalski, Jonez; Lugão, Simony Marta Bernardo (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate cassava (Manihot esculenta) crop yield, as well as soil density and carbon content, under no‑tillage and conventional cultivation, in rotation with palisade grass (Urochloa brizantha) subjected to grazing. Treatments consisted of cassava cultivated as follows: in conventional tillage after 2 (CC-2P) and 4 (CC-4P) years of pasture; in no-tillage after 2 (NTC-2P) and 4 (NTC-4P) years of pasture; and with perennial pasture (PP) of palisade grass. The CC-2P treatment showed higher cassava yield in the 2016/2017 crop year (63.29 Mg ha-1) than NTC-2P (47.85Mg ha-1). However, in the 2018/2019 crop year, no significant yield differences were observed between CC-4P (60.95 Mg ha-1) and NTC-4P (60.68 Mg ha-1). Between 2012 and 2019, soil carbon content (0–10 cm) decreased in the CC-2P treatment. In 2019, carbon stock was higher for NTC-4P compared with CC-4P and CC-2P, increasing from 16.41 to 21.46 Mg ha-1 between 2012 and 2019. Cassava yield varies depending on crop year, whereas soil carbon content decreases after CC-2P, but increases after NTC-4P.
Keywords: Manihot esculenta; Urochloa brizantha; carbon; crop-livestock integration; soil quality; straw.